Complicated COVID-19 pneumonia in an infant: A rare entity (Indian Journal of Case Reports, 2021)
In the era of the COVID-19 pandemic, children are spared from severe disease, accounting for 0.39–12.3%. According to a study in Wuhan China, only 2.7% of children are developed severe pneumonia. There are few cases reported with COVID-19 pneumonia in infants. We report the case of a 45-day-old infant who presented with respiratory distress with COVID-19 pneumonia required mechanical ventilation with an intercostal drainage tube for pyopneumothorax. The child was treated with intravenous antibiotics with supportive oxygen therapy. The fluid report of the pyopneumothorax was showing MRSA growth, so antibiotics were modified according to the sensitivity report. In this case report, COVID-19 pneumonia presented with complications in the form of pyopneumothorax with secondary bacterial infection and was successfully treated with a vigilant approach.